Half-Cauchy Chen Distribution with Theories and Applications - Chaudhary, Arun Kumar; Yadav, Ram Suresh; Kumar, Vijay (Journal of Institute of Science and Technology, 2023)
In this article, we have suggested the three-parameter half-Cauchy Chen distribution which has been derived by compounding a continuous Chen distribution with the half-Cauchy family of distribution. The hazard rate function (HRF), quantile function, reversed hazard rate function, survival function, cumulative distribution function (CDF), probability density function (PDF), kurtosis, and skewness of the suggested distribution are some of its statistical properties and characteristics that are explored. Utilizing the methods of LSE, CVM, and MLE, the parameters of the new distribution are computed. All the calculations are performed with the aid of R programming software. To assess the application of the new distribution, two real data sets are analyzed and performed the goodness-of-fit. It is found that the half-Cauchy Chen distribution outperformed a few other existing distributions. We hope that this distribution will contribute to the field of real data analysis.